2014
DOI: 10.1155/2014/438945
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Allosensitization in Low Immunological Risk Kidney and Kidney-Pancreas Graft Recipients

Abstract: Introduction. Posttransplantation allosensitization prevalence and effect on kidney grafts outcomes remain unsettled. Methods. Between 2007 and 2012, 408 patients received a primary kidney graft (with 68 patients also receiving a pancreas graft) after a negative cytotoxic crossmatch. All patients had a pretransplant negative anti-HLA screening and 0% panel reactive antibodies. We analyzed retrospectively the results of anti-HLA antibodies screening by Luminex assay, performed between 6 and 24 months after tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…1,2,8,9 This speculation is plagued by anecdotal reports, small sampling size, and considerable variation in the sensitivity of DSA detection. 1,2,8,9,14 17 However, a common observation (also seen here) is that de novo DSAs are commonly directed against class II instead of class I. 9,14 17 One longitudinal study observed that while DSAs appearing within the first postoperative year were equally directed against class I and class II, thereafter class II DSA dominated to 71% DSA+.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…1,2,8,9 This speculation is plagued by anecdotal reports, small sampling size, and considerable variation in the sensitivity of DSA detection. 1,2,8,9,14 17 However, a common observation (also seen here) is that de novo DSAs are commonly directed against class II instead of class I. 9,14 17 One longitudinal study observed that while DSAs appearing within the first postoperative year were equally directed against class I and class II, thereafter class II DSA dominated to 71% DSA+.…”
Section: Discussionsupporting
confidence: 65%
“…1,2,8,9,14-17 However, a common observation (also seen here) is that de novo DSAs are commonly directed against class II instead of class I. 9,[14][15][16][17] One longitudinal study observed that while DSAs appearing within the first postoperative year were equally directed against class I and class II, thereafter class II DSA dominated to 71% DSAþ. 9 The clinical relevance of this is actively debated.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The development of anti-HLA antibodies after transplantation (de novo anti-HLA antibodies) is also associated with reduced graft survival. In isolated pancreas or simultaneous kidney–pancreas transplantation and in islet transplantation, several reports have previously demonstrated that the development of anti-HLA antibodies after transplantation is a risk factor for graft function and graft survival (1,2,10,14). However, these studies usually include several centers with different immunosuppressive strategies and do not compare both procedures (pancreas vs. islet transplantation), with regard to the presence of anti-HLA antibodies, as an independent risk factor for graft function and graft survival.…”
Section: Introductionmentioning
confidence: 99%